Proportion of Staphylococcus aureus with a Vancomycin Minimum Inhibitory Concentration (MIC) of 1 mg/L Increases Between 2012 and 2017 in Singapore. (4th October 2017) - Mendis, Shehara M; Barkham, Timothy
Abstract: Background: Vancomycin is commonly used to treat methicillin-resistant Staphylococcus aureus (MRSA). Monte Carlo simulations in the literature suggest that vancomycin may not reach desired pharmacodynamic targets when typical dosing regimens are used to treat S . A ureus (SAU) with an MIC > 1 mg/L. Worse clinical outcomes have also been associated with methicillin-susceptible S . A ureus (MSSA) with higher vancomycin MICs, when treated with β-lactams. Methods: Vancomycin MICs (VITEK 2) for SAU isolated from June 2012 to April 2017 were collated from the laboratory records at Tan Tock Seng Hospital, Singapore. Vancomycin MICs for MSSA are underrepresented as susceptibility tests for SAU isolated from blood are initially performed by direct disk diffusion. A reflex Vitek susceptibility is performed on MRSA but not MSSA blood isolates. All nonblood isolates are assessed by Vitek. Duplicates were removed. Results: All vancomycin MICs were within the susceptible range of ≤2 mg/L (Table 1). There was an overall temporal increase in proportions of both MRSA and MSSA isolates with an MIC 1 mg/L, from 9 to 30% and 14 to 37%, respectively. There was a reciprocal decrease in the proportion of isolates with MIC ≤ 0.5 mg/L (Figure 1). Proportions with MIC 2 mg/L showed a decreasing trend. These trends remained consistent when all SAU, both MSSA and MRSA together, were split into blood isolates and "other" groups (Figure 2). The data for MRSA bacteremia were analysed separately. The proportion with MIC 1 mg/L increased from 7% in 2012 to 27% in 2017. The proportion with MIC 2 mg/L decreased from 21% in 2012 to zero since 2016. Conclusion: The proportion of Staphylococcus aureus isolates with an MIC of 1 mg/L increased more than threefold between 2012 and 2017. This trend is seen in both bloodstream and noninvasive isolates. As the proportion with MIC >1 mg/L has not increased, Monte Carlo simulations would suggest that clinical outcomes may not have been affected despite this upward creep. Disclosures: All authors: No reported disclosures.